2013
DOI: 10.2527/jas.2013-6342
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic status, gonadotropin secretion, and ovarian function during acute nutrient restriction of beef heifers1,2

Abstract: The effect of acute nutritional restriction on metabolic status, gonadotropin secretion, and ovarian function of heifers was determined in 2 experiments. In Exp. 1, 14-mo-old heifers were fed a diet supplying 1.2 × maintenance energy requirements (1.2M). After 10 d, heifers were fed 1.2M or were restricted to 0.4 × maintenance requirements (0.4M; d 0). Heifers received PGF2α (25 mg, intramuscularly) on d -10, 0, and 10 to synchronize ovulation. After 30 d, 1.2M and 0.4M heifers were realimented to 1.2 M for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
8
1
2
Order By: Relevance
“…; Lents et al . ). The decreased IGF‐1 concentration in the present study therefore also suggested a worse nutritional status in the lambs during the last 2 months of the study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Lents et al . ). The decreased IGF‐1 concentration in the present study therefore also suggested a worse nutritional status in the lambs during the last 2 months of the study.…”
Section: Discussionmentioning
confidence: 97%
“…The NR decreased drastically and the proportion of NR to NI also decreased, suggesting a worse nitrogen utilization compare with that of P1 and P2, probably due to the lowest MEI, RDPI and imbalance of CPI/MEI. The blood concentration of IGF-1 has been shown to increase with advancing age during the first year of life (Roberts et al 1990;Oldham et al 1999) and is markedly affected by nutritional status (Bossis et al 2000;Shen et al 2004;Lents et al 2013). The decreased IGF-1 concentration in the present study therefore also suggested a worse nutritional status in the lambs during the last 2 months of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Feed quality and nutritional status affect blood concentrations of IGF‐1 and GLU (Roberts et al., ; Yambayamba et al., ; Bossis et al., ; Shen et al., ; Lents et al., ). However, in our study, the serum IGF‐1 and GLU concentrations showed no significant differences between LR and C. Ebara et al.…”
Section: Discussionmentioning
confidence: 99%
“…Si la CC es baja, se forman folículos pequeños y por lo tanto, hay un retraso en el comienzo de la ciclicidad. Lents et al (26) concluyeron que la CC al momento del parto y la suplementación proteica post-parto, influyen en el tamaño del folículo dominante en el primer estro.…”
Section: Componenteunclassified
“…Varios informes, hacen referencia a que los ácidos grasos poliinsaturados pueden elevar la fertilidad de las hembras bovinas, aumentando el número y tamaño de los folículos ováricos (28,29), el tamaño del cuerpo lúteo (26,28), la calidad de los ovocitos (30) y la concentración circulante de hormonas esteroides y prostaglandinas (26, 31).…”
Section: Componenteunclassified